The Effects Of Different Logging Techniques On The Physical And Chemical Characteristics Of Forest Soil - Eroglu, Habip; Sariyildiz, Temel; Kucuk, Mehmet; Sancal, Erhan (Aperta, 2016)
In this study, we investigated the effects of four timber logging techniques (skyline, skidder, manpower and chute system) on the physical (permeability, field capacity, water holding capacity, bulk density, fine and coarse soil, sand, clay and silt ratios) and chemical properties (electrical conductivity, organic matter, total lime, P2O5K2O, Ca, Mg, Na, Fe, Zn, Cu and Mn contents) of forest soil at two soil depths (0-15 and 15-30 cm) at loading, unloading, skid road, and undisturbed plots. The logging practices, each consisting of three steps, were executed at 12 testing sites in total, where logging through skylines, ground skidding with manpower, skidding with skidders, and sliding within the chute systems were performed.
Keywords: 15. Life on land